Pathways Housing First for Homeless Persons with Psychiatric Disabilities: Program Innovation, Research, and Advocacy. (December 2013) - Greenwood, Ronni Michelle; Stefancic, Ana; Tsemberis, Sam; Massey, Sean G.; Barreras, Ricardo E.
<x xml:space="preserve">Abstract</x> This article describes how the Pathways Housing First (PHF) model of homelessness intervention evolved from a radical idea to the gold standard of service delivery for homelessness intervention programs that serve adults with psychiatric and/or substance abuse diagnoses, not only in the United States, but worldwide. Through the example of PHF we explain how the integration of rigorous research with consumer‐driven service delivery yielded an evidence‐based practice that transformed social policy and created social change. We explain how the research was used to persuade key champions and stakeholders to support funding for and dissemination of this new model of service delivery. We emphasize the practices and strategies that maximized the model's impact validity, and note some of the key challenges that were faced along the way. Through the example of PHF we aim to increase understanding of how research can be used as a tool to achieve social and political change.